Cross-cultural experimental economics and indigenous management research: Issues and contributions - Sven Horak (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2013)
Cross-Cultural Experimental Economics (CCEE) and Indigenous Management Research (IMR) are dynamic and flourishing disciplines today. Whereas the former lacks a deep understanding of the distinctive factors leading to behavioral differences so far, the latter gives priority to deep contextualization and cultural embeddedness of the research design. This paper argues that both disciplines can mutually benefit from each other. Based on a review of 23 articles, four general research fields are identified that CCEE is concerned with: fairness, cooperation, trust and norm enforcement. In these fields CCEE and IMR can meet and mutually advance knowledge: CCEE can benefit by applying increased contextualization in the future, i.e., by integrating indigenous context-specific variables explicitly into future research designs; IMR can benefit by applying a replicable quantitative research methodology enabling high-quality IMR (Tsui 2004). Both approaches will benefit from increased validity if research designs are systematically integrated in a mixed method design for future research.
Keywords: 330; culture; cross-cultural economic experiments; indigenous management research; research methods; contextualization